Development of Mobile Application for Animal Conservation: Animal Rescue - Chan, Lok Yi; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2023)
Animal conservation approaches are fast evolving in response to rapidly growing changes in the environment as well as the integration of new modern technology. The present applications for kids to learn about animal conservation are less interesting and lack interactive features that can provide kids feedback and hold their interest. Therefore, the development of a mobile application that helps young children in learning conservation information and gets them to know animals with a gamification approach is recommended. The target users for this application project are children up to 5 and 6 years old. The Animal Rescue application was built using the Multimedia Mobile Content Development (MMCD) method. This project aims to help young people learn more about animal conservation. Respondents effectively learned conservation knowledge from Animal Rescue and applied it in their daily lives. The application received positive acceptance from users as an engaging learning tool for animal protection.